Application of continuous nursing care based on hierarchical diagnosis and treatment mode in Stage II cardiac rehabilitation of patients after percutaneous coronary intervention - Dai, Zhen-Juan; Zhou, Jian-Ying; Xu, Shen-Ting; Zhang, Jian-Feng; Zhuang, Cui-Fang; Gu, Pin-Hua (Frontiers in Cardiovascular Medicine, 2022)
Objective: To explore the effect of applying continuous nursing care based on hierarchical diagnosis and treatment in Stage II cardiac rehabilitation of patients after percutaneous coronary intervention (PCI) and provide a theoretical basis for clinical nursing intervention. Methods: Patients in PCI postoperative II cardiac rehabilitation were selected and randomly divided into the experimental group (community group), the experimental group (rehabilitation group), and the control group. Patients in the control group received the routine cardiac rehabilitation management scheme, while those in the experimental groups received continuous nursing protocol based on the hierarchical diagnosis and treatment mode. All patients were compared for the cardiac rehabilitation evaluation indexes at discharge and 6 months after discharge. Results: Compared with the control group, the left ventricular ejection fraction, 6-minute walking distance test, medication compliance, and quality of life were all improved in the two experimental groups, and the differences were statistically significant (P < 0.05). The improvement in the rehabilitation group was more significant than in the community group. There were more patients with high cardiac rehabilitation compliance in the rehabilitation group than in the community group, with the difference being statistically significant (P < 0.05). Conclusion: Continuous nursing care rehabilitation based on the hierarchical diagnosis and treatment mode can improve the cardiac function of patients after PCI, enhance their quality of life, and improve their rehabilitation and medication compliance, facilitating their cardiac rehabilitation.